Gnathia grutterae sp. nov. (Crustacea, Isopoda, Gnathiidae) parasitising representatives of the Balistidae, Labridae and Tetraodontidae from Lizard Island, Great Barrier Reef, Australia - Ferreira, Maryke L.; Smit, Nico J.; Davies, Angela J. (Zootaxa, 2010)
A new species of gnathiid was collected in March 2002 and November 2005 at Lizard Island, Great Barrier Reef, Australia. Third stage pranizae taken from balistid, labrid and tetraodontid fishes were maintained in fresh sea water until their moult into males (4 days post feeding) or females (11 days post feeding). Distinctive features of the adult male cephalosome include conical superior fronto-lateral processes directed anteriorly, with 4 simple setae in a row on each process, while the mediofrontal process is inferior with a shallow conical notch dividing the anterior part of mediofrontal process in two. The male mandible has a prominent internal lobe with small tubercles forming two rows from the internal lobe up to half the length of the mandible. The adult female has a broadly rounded cephalosome, with two pairs of long simple setae laterally on the mid-dorsal area, whereas the third stage praniza has a mandible with 9 teeth, comprising two small teeth at the tip and seven large, triangular, backwardly directed teeth on the mesial margin.